Minimally Invasive Surgery for Spontaneous Intracerebral Hematoma. Real-Life Implementation Model and Economic Estimation - Mosteiro, Alejandra; Amaro, Sergi; Torné, Ramon; Pedrosa, Leire; Hoyos, Jhon; Llull, Laura; Reyes, Luis; Ferrés, Abel; de Riva, Nicolás; Mellado, Ricard; Enseñat, Joaquim (Frontiers in Neurology, 2022)
Objective Spontaneous intracerebral hemorrhage is characterized by high fatality outcomes, even under best medical treatment. Recently, minimally invasive surgical (MIS) evacuation of the hematoma has shown promising results and may soon be implemented in the clinical practice. Hereby, we intended to foresee the logistic requirements for an early hematoma evacuation protocol, as well as to evaluate in a real-life implementation model the cost-utility of the two main MIS techniques for hemorrhagic stroke (catheter evacuation plus thrombolysis and neuroendoscopic aspiration). Methods Data were obtained from the pool of hemorrhagic-stroke patients admitted to our institution during an annual period (2020–2021) and contrasted to the reported results in published trials of MIS techniques. Potential candidates for surgical treatment were identified according to the inclusion/exclusion criteria established in these trials. Then, a cost-utility analysis was performed, which explored the incremental cost per unit of health gained with a given treatment. The treatment effect was measured by differences in modified Rankin Score, and subsequently converted to quality-adjusted life years (QALY). Results Of the 137 patients admitted to our center with supratentorial spontaneous intracerebral hemorrhage in a 1-year period, 17 (12.4%) were potential candidates for the catheter evacuation plus thrombolysis technique (Minimally Invasive Surgery with Thrombolysis in Intracerebral Hemorrhage Evacuation trial, MISTIE III criteria) and 59 (43.0%) for the neuroendoscopic aspiration technique (Dutch Intracerebral Hemorrhage Surgery Trial Pilot Study, DIST criteria). The incremental cost-utility ratio was € 76,533.13 per QALY for the catheter-based evacuation and € 60,703.89 per QALY for the endoscopic-based technique. Conclusion Around 12–43% of patients admitted to hospital with spontaneous hemorrhagic stroke could be potential candidates to MIS early evacuation of the cerebral hematoma. In our real-life implementation model, the cost-utility analysis favored the neuroendoscopic evacuation over the catheter aspiration technique. Further studies are advisable as new data from the ongoing randomized trials becomes available.